New and little-known species of the genus Tachydromia Meigen (Diptera, Hybotidae) from Thailand - Shamshev, Igor; Grootaert, Patrick (Zootaxa, 2008)
Six new species of the genus Tachydromia Meigen are described from Thailand: T. doi sp. nov., T. monocercus sp. nov., T. ocellata sp. nov., T. phanensis sp. nov., T. phu sp. nov., T. tigeri sp. nov. A new species group within Tachydromia is distinguished and an updated key to the genus from the Oriental Realm is provided.